Refugee discourse in Malaysia: issues and concerns from human security perspective - Bakri Mat,; Siti Darwinda Mohamed Pero,; Ku Nurasyiqin Ku Amir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The influx of illegal immigrants (PATI) [or economic refugees] is one of the non-traditional security issues that has long plagued the Southeast Asian region. Malaysia is no exception. Despite not being a member of any international refugee-related conventions, including the 1951 Refugee Convention and the 1967 Protocol, Malaysia recorded 185,920 registered refugees and asylum seekers until August 2022 (UNHCR 2022). The government has made it an unwritten policy for refugees to be treated on a humanitarian basis. Therefore, this study was designed to explore the issues and concerns of Rohingya refugees in Malaysia from a human security perspective. This research was conducted using qualitative methodology by utilising primary sources from in-depth interviews, direct observation through participation in seminars, and field studies in selected areas in Northern Peninsular Malaysia, particularly in Kedah. The study findings concluded that there are five areas of concern that often-become obstacles to the livelihood of refugees in Malaysia, namely the right to work, education, documentation, security (due to xenophobic sentiments), and healthcare. These areas are fundamental to refugee livelihood; therefore, this research finds that it is timely for the government to formulate a more transparent and proactive policy to deal with this issue effectively.